Controlling Geminiviruses before Transmission: Prospects - Muhammad Salman Mubarik; Sultan Habibullah Khan; Aftab Ahmad; Ali Raza; Zulqurnain Khan; Muhammad Sajjad; Reda Helmy Ahmed Sammour; Abd El-Zaher M.A. Mustafa; Abdullah Ahmed Al-Ghamdi; Amal H. Alajmi; Fatin K. I. Alshamasi; Mohamed Soliman Elshikh (Plants, 2020)
Whitefly (Bemisia tabaci)-transmitted Geminiviruses cause serious diseases of crop plants in tropical and sub-tropical regions. Plants, animals, and their microbial symbionts have evolved complex ways to interact with each other that impact their life cycles. Blocking virus transmission by altering the biology of vector species, such as the whitefly, can be a potential approach to manage these devastating diseases. Virus transmission by insect vectors to plant hosts often involves bacterial endosymbionts. Molecular chaperonins of bacterial endosymbionts bind with virus particles and have a key role in the transmission of Geminiviruses. Hence, devising new approaches to obstruct virus transmission by manipulating bacterial endosymbionts before infection opens new avenues for viral disease control. The exploitation of bacterial endosymbiont within the insect vector would disrupt interactions among viruses, insects, and their bacterial endosymbionts. The study of this cooperating web could potentially decrease virus transmission and possibly represent an effective solution to control viral diseases in crop plants.